Effects of rice husk biochar and genotype rice interaction on soil fertility and growth dynamics of upland rice in rainfed dryland - Gamaruddin, Gamaruddin; Sudiarso, Sudiarso; Suryanto, Agus; Soemarno, Soemarno; Agustina, Rohmatin (Journal of Degraded and Mining Lands Management, 2026)
Upland rice productivity in rainfed drylands of Eastern Indonesia remains constrained by severe soil degradation and suboptimal agronomic management. This study evaluated the combined effects of rice husk biochar (0, 5, 7.5, and 10 t ha-¹) and four upland rice genotypes on soil fertility improvement and growth dynamics across three physiological phases. A factorial randomized complete block design with three replications was implemented in Majene Regency, West Sulawesi. Results showed that biochar selectively improved the most degraded soil properties, increasing organic C (+13.4%), total N (+20-27%), and available phosphorus (+26.6%), while exchangeable potassium and C/N ratio remained unchanged. Soil improvements were consistent across genotypes, as no significant genotype × biochar interaction was detected. However, growth responses were strongly genotype-dependent, with significant interactions observed for plant height, tiller number (p<0.05), and crop growth rate (p<0.01). Temporal analysis identified the peak vegetative phase as the critical window for treatment differentiation. The Asseang genotype exhibited superior performance, achieving the highest plant height (115.7 cm), tiller number (21.3), and crop growth rate (9.12 g m-² day-¹). The optimal biochar dose was 7.5 t ha-¹, beyond which growth responses plateaued, highlighting the need for integrated genotype–biochar strategies for sustainable intensification.